FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING SECARA VOLUNTARY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PAD BURSA EFEK INDONESIA - Wangge, Maria Fransiska H; Banda, Falentina L; Thalib, Sabra B Wahab (Program Studi Akuntansi Universitas Flores, 2021)
This study aims to determine the effect of management change, audit opinion, client size and financial distress on voluntary auditor switching at manufacturing companies listed on the Indonesia Stock Exchange for the period 2010-2014. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange. The number of manufacturing companies that were sampled using the purposive sampling method was 64 companies for 5 years of observation. Hypothesis testing in this study uses logistic regression analysis. Based on the results of the logistic regression test, the results of this study indicate that the independent variable management change, audit opinion, client size and financial distress have a negative effect on the dependent variable auditor switching voluntarily.